'[I]T WAS REMARKED THAT HE WOULD NOT HAVE DONE IT WITHOUT GOOD REASON': CONCEALING NOBLE IDENTITY THROUGH REDEFINING ILLEGALITIES IN MARIE DE FRANCE'S 'BISCLAVRET'. (2015) - Kieser, Micheal
No abstract available